PRESIDENTIAL SPEECH: EXPLORING JOKO WIDODO IN HANDLING COVID-19 CASES - Cecep Agus,; Rindy Kartika lapian,; Aisah, Aisah (JOEL: Journal of Educational and Language Research, 2023)
Speech is the process of using language, which means knowing or being able to choose words that can affect how people communicate. Discourses can convey the contemplations, information, or considerations of the speaker to the whole populace and want to convince the crowd. This study aims to determine how President Jokowi's virtual speech uses presuppositions to describe the Corona Virus Handling Problem. This study used excerpts from President Jokowi's speech taken from articles on Bisnis.com as its data. The information is then dissected and categorized into six types of presuppositions using presuppositions. Only three of the six types of presuppositions that were discussed in the previous section were utilized by President Jokowi in his speech, particularly factual, lexical, and relational words. President Jokowi made frequent use of this factual presumption in his speech. presumption of facts, which President Jokowi typically employs in his speeches